SERVICE QUALITY ANALySiS OF PHARMACY MANAGEMENT INFORMATION SYSTEM IN ACADEMIC HOSPITAL OF GADJAH MADA UNIVERSITY - Arifin Santoso; Hari Kusnanto; M. Lutfan Lazuardi (Faculty of Pharmacy, Universitas Gadjah Mada)
To improve the quality of service, a hospital needs a management information system that always follow the development of information technology. If the system does not provide the required information, the user will not satisfied and look for other alternatives. Satisfaction of the users can be used to evaluate the quality of information systems in organization. This study aimed to evaluate the quality of pharmacy management information system in academic hospital of Gadjah Mada University and to know theobstacles and benefits perceived by the user with customer window analysis. This study was descriptive research, with survey method. The subjects in this study were physician, pharmacist and IT Officer. The data were analyzed using SERVQUAL and Customer Window Analysis The result showed that there was negative gap value between expectations and perception of the user management information systems of the hospitals. Therefore all of the user experienced dissatisfaction with the management information systems. The biggest gap was in dimensions of assurance (-1,36) followed by dimensions of esponsiveness (-1,35), reliability (-1,15), tangibles (-1,1) and empathy (-0,94). Meanwhile, the largest gap in the information service quality was the format (-1,92), followed by completeness (-1,35), timeliness (-1,17), accuracy (-1,08), security (-1,00), ease of use (-0,98) and socio cultural (-0,96). From the analysis of customer window, the priorities of improvement were in the dimension of responsiveness, assurance and format.Keywords: Quality, Management information system RSA UGM, SERVQUAL, Customer Window Analysis